High prevalence of fecal carriage of extended-spectrum beta-lactamase producing Enterobacterales among patients with urinary tract infections in rural Tanzania - Macha, Magreth Erick; Qi, Weihong; Seiffert, Salome N.; Bösch, Anja; Kohler, Philipp; Urassa, Honorathy Msami; Haller, Sabine; West, Erin; Rohacek, Maja Weisser; Babouee Flury, Baharak (Frontiers in Microbiology, 2025)
IntroductionThe global rise of extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-PE) challenges resource-limited countries with insufficient laboratory infrastructure. This study investigates fecal carriage and risk factors for ESBL-PE and carbapenemase-producing organisms among patients with urinary tract infection (UTI) in rural Tanzania.MethodsThis cross-sectional study was conducted at St. Francis Regional Referral Hospital, Ifakara, Tanzania, from October 2021 to August 2023, involving 326 UTI patients. Demographic data and resistance risk factors were collected via structured questionnaires. Stool samples collected pre-antibiotic treatment were screened for ESBL-PE and carbapenemase locally. Positive samples underwent further analysis in Switzerland using MALDI-ToF, Vitek MS, and whole-genome sequencing. Multivariable analysis assessed predictors associated with ESBL-PE carriage for risk factors with p < 0.05.ResultsWe enrolled 326 UTI patients (median age: 35.5 years, range: 25–52) and 189 (58.0%) were females. Fecal ESBL-PE colonization was detected in 70.9% of patients, predominantly E. coli (62.8%) and K. pneumoniae (33.0%). Whole-genome sequencing identified diverse phylogroups and sequence types, with CTX-M-15 being the most common ESBL gene. IncF plasmids were the primary carriers. Younger age (aOR: 0.98, 95% CI: 0.97–0.99; p = 0.0239) and inpatient status (aOR: 1.77, 95% CI: 1.08–2.91; p = 0.0036) were significant risk factors for ESBL-PE carriage.ConclusionThe high prevalence of ESBL-PE fecal carriage in rural Tanzania highlights the need for improved infection control and further research into community transmission dynamics.